Molecular typing and drug resistance analysis of carbapenem-resistant Klebsiella pneumoniae from paediatric patients in China - Zhang, Xian; Xue, Jian; Shen, Mei-Jing; An, Wen-Hong; Chen, Ze-Qiong; Wu, Kai-Feng (The Journal of Infection in Developing Countries, 2022)
Introduction: There are few studies on paediatric carbapenem-resistant Klebsiella pneumoniae (CRKP) in China. The present study investigated the molecular epidemiological and drug resistance characteristics of CRKP from paediatric patients in China to provide a reference for the prevention and control of CRKP infection. Methodology: In total, 20 nonrepetitive clinical CRKP isolates were collected between February 2019 and February 2020 in a tertiary hospital in China. Strain identification and drug susceptibility testing were carried out using the VITEK® 2 Compact Bacterial Identification and Monitoring System. Sequence typing, phylogenetic relationships, and antibiotic resistance-associated genes were analysed by whole genome sequencing (WGS). Results: sequence typing (MLST) and Core genome multilocus sequence typing (cgMLST) analysis revealed the most frequently represented were ST2407-CT3536 (30%), ST76-CT5893 (25%), and ST309-CT7864 (25%). All 20 CRKP isolates were divided into three clusters. All isolates were highly resistant to a variety of β-lactams and were highly susceptible to quinolones, aminoglycosides, and sulphonamides. All isolates mainly carried the carbapenem resistance genes blaNDM-1 and blaKPC-2, among which 10 isolates carried both blaNDM-1 and blaKPC-2 simultaneously. Conclusions: Sequence typing, phylogenetic relationships, and antibiotic resistance genes can be determined using WGS technology. This can guide CRKP infection control and clinical treatment for paediatric patients.